Sufistic Values in Suryomentaram Kawruh Jiwo - Nikmaturrahmah Nikmaturrahmah; Ahmad Musyafiq (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
The teaching of Sufism contains the noble values. The noble values can also be found in a variety of Javanis traditions and local wisdom, one of them is Kawruh Jiwa Ki Ageng Suryomentaram. The concept of Kawruh Jiwa is a method to achieve the soul condition without ego, it’s also called “man without attribute”, is relevant to the teachings of Sufism in the fight against the lust, and pursue the noble values of Sufistic wisdom. This study intends to reveal the Sufistic values in Kawruh Jiwa Ki Ageng Suryomentaram, by analyzing the relevance between the values in maqamat and ahwal with Kawruh Jiwa concept. The results showed that the concept of Kawruh Jiwa relevance to the values of maqamat and ahwal such as repentance (tawbah), asceticism (zuhd), patient (sabr), confidence (tawakkul), mujahadah, qanaah, tawadhu, and itsar. Thus, it can be said that the Kawruh Jiwa relevance with the Sufistic noble values, and reinforce those values in the frame of local wisdom.